Analisis Peran Kepemimpinan Kepala Puskesmas dalam Pelaksanaan Layanan Komprehensif Berkesinambungan HIV-IMS di Kota Semarang - Noor Fadhilah Dyah Anggraini; Sutopo Patria Jati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Semarang City in 2015 get the first position in the prevalence of HIV case in Central Java. Eventhough all of theprimary health care in Semarang City already got the training in sustainable comprehensive cervices, the implementations still has a limitation because of the coordination problem. Chief of primary health care have a great roles in sustainable comprehensive services (SCS) implementation. This study aim to identify the roles of primary health care Chief in the SCS implementation with 6 pillars in Semarang City primary health care. Qualitative and descriptive approach used for this study. All of the data was collected with in-deth interview. Key informants were four primary health care Chief in Mijen and North Semarang region. Triangulation informants were six people who works as Sustainable Comprehensive Services Coordinator in primary health care and City Health Office in Semarang City. From this study we can conclude that interpersonal roles in primary health care Chief as the mediator were not optimal. primary health care Chief was not actively involved and not coordinating well with the HIV-IMS SCS organization. In the informational roles, primary health care Chief was not acting as resources and spokesperson himself. primary health care Chief was fulfilling their duties in decisional roles but there is still problem in mediation and problem solver in SCS team. This study suggests that primary health care Chief should make a good relation, communication, and cooperation with other parties which associated with HIV-IMS SCS, more active in attending related SCS activities and may provide a solution and act decisively when there are problems with the SCS team.